PROBLEMATIKA TINDAK PIDANA ITE DALAM PERSFEKTIF SISTEM HUKUM - Firmansyah (FAKULTAS HUKUM UM PAREPARE, 2017)
Criminal Act of ITE or cyber crime is a new form of dimension of crime of the present which previously did not know, then the necessary tools to accommodate criminal acts committed in cyberspace, such as the Law related to it, this Journal aims to know the related Problems the problem of the crime of ITE as well as to know the efforts of handling ITE crime. This journal uses the normative juridical method. While the analysis with descriptive method kualitatif. The results of this paper Cybercrime problem is a very complex issue both related to legal issues, such as jurisdiction issues that are Problems related to power or authority, namely who is in charge of the internet world, Another issue is related to ethics and morals related to good and bad values and the steps taken in cyber crime is focused on the substance of regulatory issues namely the harmonization of rules of law in various countries, the problem of structures in which the state must be pro-active such as attending international forums related to cyber crime, giving training to the apparatus, and from legal culture is a paradigm shift related to Cyber crime as a criminal act.